Amino acid formulas in patients with food allergy - Alexander A. Baranov; Leyla S. Namazova-Baranova; Anna A. Alexeeva; Eduard T. Ambarchian; Lianna K. Aslamazyan; Natalia G. Astafieva; Larisa A. Balykova; Irina A. Belyaeva; Vilya A. Bulgakova; Irina V. Vakhlova; Nato D. Vashakmadze; Elena A. Vishneva; et al. (Педиатрическая фармакология)
The article presents modern approaches to the use of balanced formulas for nutrition and diet correction in children with various forms of food allergies. The guidelines are based on all available up to date evidence on the efficacy, safety and utility of using such innovative medical technology as specialized amino acid formulas. This formula is the targeted medical intervention for food allergies and confirmed cow's milk protein allergy, and particularly for patients with reduced physical growth and development (growth rates included). The material is based on methodological guidelines on the amino acid formulas usage previously developed by specialist experts of the Union of pediatricians of Russia in 2020.